Analysis of mortality and risk of death in HCV- and HCV/HIV-infected patients with extrahepatic manifestations - N. V. Dunaeva; Yu. I. Ulitina; E. Yu. Kolpashchikova; S. Yu. Romanova; D. A. Gusev (Журнал инфектологии)
The aim of the study was to analyze the mortality of patients infected with the hepatitis C virus (HCV) and co-infected with the human immunodeficiency virus (HIV) with extrahepatic manifestations associated with cryoglobulinemia, and to assess the dependence of the risk of fatal outcome on such predictors as the presence of HIV infection, the presence of cirrhotic liver transformation, antiviral therapy (AVT) of chronic hepatitis C, cryoglobulin levels.Materials and Methods. The prospective study included 125 patients with HCV (n=92) and HCV/HIV infection (n=33) who had extrahepatic manifestations (arthralgia and/or skin hemorrhagic rashes and/or polyneuropathy and/or or Raynaud’s syndrome and/or xerophthalmia and/ or chronic kidney disease), as well as cryoglobulins.Results. 19 out of 125 patients (15% (95% CI 10-23%)) died in the follow-up period from 1 to 170 months (median 57 months), among which 12 people did not receive AVT for HCV infection during the follow-up period and 7 patients underwent AVT during the observation period. Unadjusted mortality among patients treated with AVT was 9% (95% CI 5–18%) (n=7/77), those who did not receive it was 25% (95% CI 15–39%) (n=12/48), χ2=5,806, p=0,016. Cox regression analysis showed that an increase in the risk of death is associated with the presence of cirrhotic liver transformation by 5,3 times and the absence of AVT by 3,7 times. The main causes of death in 69% of cases were causes not associated with liver pathology, in 26% were complications of liver cirrhosis (bleeding or progressive encephalopathy), in one case (5%) the cause of death remained unknown.Conclusions. Мortality among patients with HCV or HCV/HIV infection complicated by the development of extrahepatic manifestations associated with cryoglobulinemia is higher in the absence of AVT than in the case of AVT. Cirrhotic liver transformation and the absence of AVT significantly affect the risk of death. Patients with extrahepatic manifestations die mainly from causes not associated with liver pathology.